Let’s get some food! The influence of marital status on the attributes’ perception of food delivery applications - Zanquet, Monique Aparecida; Tezza, Rafael; Kieling, Ana Paula (Revista de Administração da UFSM, 2024)
Purpose: This research aims to identify the influence of marital status on the attributes’ perception of food delivery applications (FDA) by Brazilian consumers, considering convenience, price, usability, various food choices, and trustworthiness. Methodology: This quantitative research study is based on a survey with a sample of 348 Brazilian FDA users, applying exploratory factor analysis (EFA). Findings: This article sought to answer the influence of marital status (considering people married or in a common-law marriage vs. single, separated, and divorced individuals) on the consumer’s perception of attributes of food delivery applications (FDAs). The attributes analyzed were price, convenience, usability, various food choices, and trustworthiness. The results demonstrate differences between the groups, with single, separated, and divorced individuals emphasizing perceptions of the FDA attributes usability and price. Theoretical contributions: The study extends the theory on m-commerce and FDAs, as well as managerial implications for companies in the food delivery sector. Armed with such knowledge, marketing managers can develop strategies focusing on specific interest groups according to marital status, considering the attributes of greatest value for each segment. Relevance/Originality: The increase in FDA consumption has attracted the attention of the most diverse market segments. This study brings light to new propositions concerning purchase habits by specific groups, reinforcing the need to improve communication between company and user, counting on resources such as customization and segmentation to optimize the use of apps.